2019
DOI: 10.1111/jasp.12582
|View full text |Cite
|
Sign up to set email alerts
|

“I changed and hid my old ways”: How social rejection and social identities shape well‐being among ex‐prisoners

Abstract: Being a member of a rejected group negatively affects well‐being but can also increase group identification, which can have positive effects on well‐being. However, this rejection‐identification model has never been investigated among the highly stigmatized group of ex‐prisoners. Furthermore, the potential buffering role of multiple group memberships has never been investigated within the rejection‐identification model. We conduct a novel investigation of a combined rejection‐identification and social cure mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 59 publications
(93 reference statements)
0
24
0
Order By: Relevance
“…In addition, people with low socioeconomic status perceive greater pressure in close relationship [42], lower trust level [43], increase adverse childhood experience/maltreatment [44], and face more community violence and higher conflicts [45], which are not conducive to the improvement of community identity for people with low socioeconomic status. And that the social cure effect suggest that low community identity can cause individuals' ill-health outcome [25], enhance depression [26,29,30], decrease satisfaction with life [32] and well-being [30,33]. Therefore, community identity mediates the effect of socioeconomic status on sense of gain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, people with low socioeconomic status perceive greater pressure in close relationship [42], lower trust level [43], increase adverse childhood experience/maltreatment [44], and face more community violence and higher conflicts [45], which are not conducive to the improvement of community identity for people with low socioeconomic status. And that the social cure effect suggest that low community identity can cause individuals' ill-health outcome [25], enhance depression [26,29,30], decrease satisfaction with life [32] and well-being [30,33]. Therefore, community identity mediates the effect of socioeconomic status on sense of gain.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, using longitudinal two-wave design and field-experimental design, researcher [25] found social identity positively affect perceived social support, which, in turn, positively affect collective self-efficacy, thereby reducing individuals' ill-health outcomes, such as emotional exhaustion, chronic stress, and depressive symptoms. An emerging research approach, named as the social cure effect, claimed that social identity would promote well-being and mental health, alleviate depression [26][27][28][29][30]. Moreover, the social cure effect can be found in diverse group and context, such that social identity was associated with depressive symptom among older adults [31], greater satisfaction with life among homeless people [32] and more hedonic and eudaimonic well-being among voluntary and forced refugees [33].…”
mentioning
confidence: 99%
“…This finding is especially powerful because previous research has theorised (e.g. Jetten et al, 2017) and shown (Kyprianides, Easterbrook, & Cruwys, 2019) that, for stigmatised groups, there are boundary conditions under which the "social cure" associated with multiple groups can transform into a "social curse"-whereby having multiple groups may actually be harmful for wellbeing. We were, however, able to show that the beneficial effects of multiple group memberships are not jeopardised for this population.…”
Section: The Importance Of Individual and Group Ties For Prisoner Welmentioning
confidence: 98%
“…However, the rejection‐(dis)identification model did not always receive empirical support (e.g., Bobowik, Martinovic, Basabe, Barsties, & Wachter, 2017; Jasinskaja‐Lahti et al, 2009). For example, inconsistencies in this literature were found regarding the effects of identification on well‐being in the context of especially stigmatized groups (e.g., those suffering depression: Cruwys & Gunaseelan, 2016; and ex‐prisoners: Kyprianides, Easterbrook, & Cruwys, 2019). Moreover, in the contexts of ethnic‐based rejection, the rejection‐(dis)identification model has received only partial support, with some results that did not confirm the theoretical predictions (Bobowik et al, 2017; Wiley, Lawrence, Figueroa, & Percontino, 2013).…”
Section: Introductionmentioning
confidence: 99%